2021
DOI: 10.21608/ejchem.2021.86987.4221
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, Antioxidant and Antimicrobial Activities of Lignin and Eco-friendly Lignin Nanoparticles from Egyptian Cotton Stalks

Abstract: Pathogenic microorganisms are a major source of environmental concerns, according to their capability of proliferation on all surfaces. Antimicrobial drugs of new types are now has been developed to inhibit bacteria adherence and biofilm formation. However, they are generally of synthetic origin and have a lot of disadvantages. Natural biopolymers as cellulose, hemicellulose, and lignin, look interesting as antibacterial agents. Lignin, a common plant biopolymer, is known to have antioxidant activity. Nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The antibacterial efficacy of the PVA/chitosan/V 2 O 5 nanoparticles was increased by increasing the V 2 O 5 nanoparticle concentration. [74][75][76][77][78] As one will notice, in the past few years the progress in the quest for achieving excellence with respect to wash fastness, antibacterial attributes and the biocompatibility of textile materials in comparison with using only nanoparticle coating has been quite significant and is ongoing. By using nanoparticles-biopolymers deposition on textiles by various deposition techniques, the antibacterial attributes and the biocompatibility of the textile materials can easily be achieved simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial efficacy of the PVA/chitosan/V 2 O 5 nanoparticles was increased by increasing the V 2 O 5 nanoparticle concentration. [74][75][76][77][78] As one will notice, in the past few years the progress in the quest for achieving excellence with respect to wash fastness, antibacterial attributes and the biocompatibility of textile materials in comparison with using only nanoparticle coating has been quite significant and is ongoing. By using nanoparticles-biopolymers deposition on textiles by various deposition techniques, the antibacterial attributes and the biocompatibility of the textile materials can easily be achieved simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial efficacy of the PVA/chitosan/V 2 O 5 nanoparticles was increased by increasing the V 2 O 5 nanoparticle concentration. 7478…”
Section: Discussionmentioning
confidence: 99%
“…11 (2023) carbohydrate composed of oxygen, carbon, and hydrogen, with several properties of cellulose depending on the degree of polymerization, chain length, and the number of glucose units comprising the polymer chain. Natural biopolymers as cellulose, hemicellulose, and lignin, showed antibacterial activities [12]. Cellulose is insoluble in water, weak acids, alkalis, and most organic solvents [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is insoluble in water, weak acids, alkalis, and most organic solvents [13]. Lignin, a common plant biopolymer, is known to have antioxidant activity and its nanoparticles showed a significant power to inhibit bacterial growth over time [12]. Recently, industrial production of most chemicals relies on fossil-based feedstock [14].…”
Section: Introductionmentioning
confidence: 99%
“…syringae and the antibacterial activity was observed with good efficiency. Ali et al (2022 ) prepared lignin nanospheres from cotton by-products by the organosolv technique. It was observed that obtained materials exhibited great antibacterial properties, several times higher than conventional antibiotics.…”
Section: Introductionmentioning
confidence: 99%